2018
DOI: 10.1177/0887403418804871
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness Stigma: Limitations of Crisis Intervention Team Training

Abstract: As police departments in the United States strive to improve their capacity to effectively engage individuals with mental illness (IMI), Crisis Intervention Team (CIT) training has become increasingly common. Limited empirical work has studied the effectiveness of CIT, and available studies demonstrate split evidence on the effectiveness of the approach. Variation in previous findings may indicate that CIT inadequately addresses key factors that create challenges for officers when engaging IMI, such as mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Scholars have hypothesized that the tools provided by CIT training increase officers’ ability to communicate and reduce their reliance on force and arrest (Haigh et al, 2020; Watson et al, 2010), especially when interacting with persons with mental illness. In line with this, Skeem and Bibeau (2008) found that CIT officers in Las Vegas, Nevada, used force in only 15% of the 189 incidents in which a risk of violence was observed; however, their study did not include a comparison group.…”
Section: Cit Trainingmentioning
confidence: 99%
See 3 more Smart Citations
“…Scholars have hypothesized that the tools provided by CIT training increase officers’ ability to communicate and reduce their reliance on force and arrest (Haigh et al, 2020; Watson et al, 2010), especially when interacting with persons with mental illness. In line with this, Skeem and Bibeau (2008) found that CIT officers in Las Vegas, Nevada, used force in only 15% of the 189 incidents in which a risk of violence was observed; however, their study did not include a comparison group.…”
Section: Cit Trainingmentioning
confidence: 99%
“…Third, we are not aware of any research that examines the relationship between CIT training and suspect compliance. However, based on the training’s focus on verbal communication and de-escalation strategies, as well as the evidence in prior research that the training may reduce the need to use force (Center for Health Policy, Planning and Research, 2007; Compton et al, 2015; Haigh et al, 2020; Skeem & Bibeau, 2008; Watson et al, 2010), we expect CIT training of correctional staff to be related to higher compliance during incidents. CIT officers may use strategies they learned in training right away as an interaction with an incarcerated person begins or as directives are being given, or they may use them as a response to initial noncompliance.…”
Section: The Current Study: Cit Training In Correctionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aside from issues surrounding job mobility, manifold other problems contribute to the intransigence of community blight that defy a quick fix, especially homelessness, drug addiction, and mental illness. The mentally ill inhabiting the area [41] require the expertise of trained professionals; [41] even police who are called to deal with troubled residents find this population to be especially challenging and fraught [42][43][44]. The move toward the deprivation of liberty of the mentally ill reveals the intractable nature of these problems and speaks to the extremity of the hurdles found in blighted communities.…”
Section: Entrenched Social Problemsmentioning
confidence: 99%